2017
DOI: 10.1186/s13018-017-0669-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive quantification of age-related changes in the vertebral endplate in rats using in vivo DCE-MRI

Abstract: BackgroundSmall animal models that can mimic degenerative disc disease (DDD) are commonly used to examine DDD progression. However, assessments such as histological studies and macroscopic measurements do not allow for longitudinal studies because they can only be completed after the animal is sacrificed. Dynamic contrast-enhanced MRI (DCE-MRI) may provide a reliable, non-invasive in vivo method for detecting the progression.MethodsThe present study investigated the progression of changes in lumbar discs and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…[14] proposed a Gabor wavelet-based intervertebral disc localization algorithm, which used the gray ratio of the two and the height information of the intervertebral disc to achieve the classification of intervertebral disc degenerative changes. [15] found that MRI T2 mapping imaging technology could not only quantitatively assess the degree of lumbar intervertebral disc degeneration but also reflect the differences in the degenerative degrees of intervertebral discs in different levels through the T2 values of the nucleus pulposus, providing imaging basis for disease diagnosis. Through the clinical research, [16] found that CT and MRI had certain advantages in the clinical diagnosis of lumbar disc herniation, and the combined application of CT and MRI could reduce the rate of missed diagnosis if necessary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[14] proposed a Gabor wavelet-based intervertebral disc localization algorithm, which used the gray ratio of the two and the height information of the intervertebral disc to achieve the classification of intervertebral disc degenerative changes. [15] found that MRI T2 mapping imaging technology could not only quantitatively assess the degree of lumbar intervertebral disc degeneration but also reflect the differences in the degenerative degrees of intervertebral discs in different levels through the T2 values of the nucleus pulposus, providing imaging basis for disease diagnosis. Through the clinical research, [16] found that CT and MRI had certain advantages in the clinical diagnosis of lumbar disc herniation, and the combined application of CT and MRI could reduce the rate of missed diagnosis if necessary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our data clearly show an age-dependent loss of IVD fluidity, as seen in the inverse correlation of STIR intensity of both AAF and NP in discs of different age. This is a known result of a concurrent loss of collagen/proteoglycans and water content predominantly in the NP [ 21 , 22 ]. Additional linear regression analysis revealed a significant reduction of density in the AAF per year of age, which was close to 1 HU per year in the cMap.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Likewise, it was also recognized as the gold standard imaging modality to evaluate the link between endplate degeneration and disc issues. 28 Several MRI techniques have been developed to study in detail the endplate structures involved in IDD and LBP. 29,30 MRI scanners with various magnetic strengths ranging from 0.25 to 9.4 Tesla have been used (Table 1), with 1.5 and 3 Tesla MRI scanners being the most common.…”
Section: Diagnostic Role Of Mri In Low Back Painmentioning
confidence: 99%